2016
DOI: 10.2147/dmso.s123244
|View full text |Cite
|
Sign up to set email alerts
|

Acarbose promotes remission of both early and late dumping syndromes in post-bariatric patients

Abstract: ObjectiveAcarbose is a glucosidase inhibitor that slows carbohydrate digestion. It could thus be effective to promote remission of dumping syndrome (DS). Previous studies associating acarbose and late dumping, although not early dumping, have been reported. Herein, we aimed to evaluate the role of acarbose in dumping syndrome prevention and treatment and in resistive exercises resistance in bariatric subjects.MethodsBariatric patients with DS and complete adherence to diet plan and resistive exercises were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Current treatment for dumping syndrome includes pharmacological and surgical interventions. Dietary supplements (pectin, guar gum, acarbose 25-30 ), somatostatin analogs (pasireotide, 5,31-33 octreotide 31 ), miglitol, 34-36 iraglutide, 37 exendin-(9-39), 38 and diazoxide 39 are prescribed for postprandial hypoglycemia or hyperglycemia caused by dumping syndrome. The GLP-1 receptor blocker can improve hypoglycemia caused by dumping syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment for dumping syndrome includes pharmacological and surgical interventions. Dietary supplements (pectin, guar gum, acarbose 25-30 ), somatostatin analogs (pasireotide, 5,31-33 octreotide 31 ), miglitol, 34-36 iraglutide, 37 exendin-(9-39), 38 and diazoxide 39 are prescribed for postprandial hypoglycemia or hyperglycemia caused by dumping syndrome. The GLP-1 receptor blocker can improve hypoglycemia caused by dumping syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, they are used as a second line medication often in conjunction with metformin (36). Evidence also exists that Acarbose can reduce dumping syndrome after bariatric surgery (11). A host of natural plant products with amylase inhibitor activities have been proposed or studied as a treatment for diabetes but little conclusive evidence exists for their effectiveness.…”
Section: Amylase Inhibitors In Clinical Medicinementioning
confidence: 99%
“…53 Indeed, several investigators have used CGM systems and found that glucose variability is exaggerated after gastric bypass, that subgroups exists according hyperglycemic pattern in these patients, and that treatment with diet and accarbose improves glycemic excursions. 54…”
Section: The Use Of Continuous Glucose Monitoringmentioning
confidence: 99%
“…A number of short-term studies involving the ingestion of up to 15 g of guar gum or pectin with each meal have demonstrated the efficacy of these dietary supplements in slowing gastric emptying, reducing GI hormone release, improving hyperglycemia, and controlling dumping symptoms (Table 2). [48][49][50][51][52][53][54][55][56][57] A single study reported that glucomannan significantly improved glucose tolerance but had no effect on glucose absorption in children with dumping syndrome who underwent various types of gastric surgery. 57 However, the palatability and tolerability of many dietary supplements are poor.…”
Section: Dietary Supplements (Level Of Evidence: Iii; Grade Of Recommmentioning
confidence: 99%
See 1 more Smart Citation